The Athens-Lübeck Questionnaire: a tool to discriminate between subtypes of persistent postural perceptual dizziness - Evangelos Anagnostou; Georgios Armenis; Athena Zachou; Renana Storm; Andreas Sprenger; Andreas Sprenger; Christoph Helmchen (Frontiers in Neurology)
IntroductionPersistent Postural-Perceptual Dizziness (PPPD), as an umbrella term for functional dizziness, encompasses a wide range of subjective symptoms affecting visual, vestibular, and motor functions. We developed the Athens-Lübeck Questionnaire (ALQ) as a bedside tool to differentiate specific symptom subtypes, which could inform more targeted research into the pathogenesis of the syndrome and facilitate tailored physiotherapeutic interventions.MethodsA total of 96 patients with primary or secondary PPPD were included in a prospective cross-sectional study conducted at two tertiary referral centers. All participants had unimpaired vestibular function, as verified by video head-impulse testing at the time of examination. Each participant completed the ALQ, an 8-item questionnaire divided into four symptom subtypes: ALQvis (visual intolerance), ALQstand (intolerance to quiet standing or sitting), ALQpass (passive motion intolerance), and ALQact (active motion intolerance). We assessed the reliability of the questionnaire, the prevalence of different symptom subtypes, and the presence of dominant symptom profiles.ResultsThe ALQ demonstrated good internal consistency, with a Cronbach’s alpha of 0.813. Items within the same symptom domain showed strong inter-item correlations. Approximately two-thirds of the participants exhibited a predominant symptom subtype, with the majority classified under the ALQact phenotype.ConclusionThe 8-item ALQ is a valid tool for identifying distinct PPPD symptom subtypes. Its primary strengths lie in its brevity and ease of use in outpatient vertigo clinics, enabling the identification of predominant phenotypes that may be relevant for guiding tailored therapeutic interventions.